Natural deep eutectic solvents (NADES) for the extraction of bioactives: emerging opportunities in biorefinery applications - Jauregi,Paula; Esnal-Yeregi,Leire; Labidi,Jalel (PeerJ Analytical Chemistry, 2024)
Natural deep eutectic solvents (NADES) have emerged as an eco-friendly alternative for extracting bioactives, avoiding the use of flammable organic solvents and extreme temperatures and pH conditions. NADES rely on intermolecular interactions between hydrogen bonding donors (HBD) and hydrogen bonding acceptors (HBA) to form eutectic mixtures with significantly lower melting points than their individual components. These matrices are influenced by factors like water content, temperature, and component ratios. NADES high viscosity can hinder extractive efficiency, which can be mitigated by adding water or working at higher temperatures. However, excessive dilution with water may disrupt the supramolecular structure of NADES, reducing extraction efficiency. A notable feature of NADES is their fine-tunability for specific purposes. Adjusting physicochemical properties such as polarity, pH, and viscosity optimizes extraction efficiency by promoting the solubility of target molecules and interactions between the NADES and target molecules. NADES, unlike organic solvents, can partially disrupt plant and microalgae cell walls, enhancing permeability and extraction efficiency. Moreover, NADES can have a stabilising effect on bioactives and can enhance their biological activity and bioavailability. These attributes, coupled with their low environmental impact in terms of low toxicity and high biodegradability, make NADES attractive for biorefinery applications.
Keywords: Natural deep eutectic solvents; Biorefinery; Physichochemical properties; Bioactives; Microalgae